Digital Libraries: For Cultural Heritage, Knowledge Dissemination, and Future Creation 13th International Conference on Asia-Pacific Digital Libraries, ICADL 2011, Beijing, China, October 24-27, 2011. Proceedings - Xing, Chunxiao; Crestani, Fabio; Rauber, Andreas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 13th International Conference on Asia-Pacific Digital Libraries, ICADL 2011, held in Beijing, China, in October 2011. The 33 revised full papers, 8 short papers and 9 poster papers presented were carefully reviewed and selected from 136 submissions. The topics covered are digital archives and preservation; information mining and extraction; medata, catalogue; distributed repositories and cloud computing; social network and personalized service; mobile services and electronic publishing; multimedia digital libraries; information retrieval; and tools and systems for digital library.
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Database Management; Computer Communication Networks; Data Mining and Knowledge Discovery